PENYELESAIAN SENGKETA PADA AKAD MURABAHAH DENGAN PENDEKATAN NON LITIGASI DI KSPPS BTM MULIA BABAT LAMONGAN - Muhammad Fahmi Azis; Isma Swadjaja (Jurnal Justisia Ekonomika: Magister Hukum Ekonomi Syariah, 2020)
ABSTRACTDisputes are disputes, disputes or disputes that occur between one party and another related to valuable rights in the form of money or property.Shari'ah economic disputes are the domain of disputes in business or trade activities. Shari'ah economic disputes can occur before or after the agreement is agreed, for example regarding the object of the agreement, the price of goods, and the contents of the agreement (Akad).In this case, this research focuses on the resolution of non-litigation sharia economic disputes on the murabahahh contract and the application of the murabahahh contract in Bspm Mulia Babat.This research is a descriptive qualitative research is a research method to make a picture of a situation or event, so that it is desirable to hold the accumulation of basic data using the method of observation, interviews, and documentation. The results of the study are that the resolution of non-litigation sharia economic disputes in the murabahahh contract in the compt btm noble tripe uses the system of family, peace, deliberation (sulhu) and the application of murabahah contract in accordance with Islamic economic principles and principles.         Keywords: Dispute Resolution, Non Litigation and Murabahahh Agreemen